2019
DOI: 10.1007/s12046-019-1105-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and tribological properties of Al7475-SiCp composites by stir casting method and wear rate modeling using RSM

Abstract: The microstructure, mechanical and wear properties of the Al 7475-SiC p composites and to investigate the effects of SiC micro-particles reinforcement with alloy have been studied. Al 7475-SiC p composites have been developed by a stir casting method. The SiC p size in the range of 15-40 lm with weight.% of 0, 5, 10 and 15 were injected in molten Aluminum 7475 alloy in argon gas environment and stirrer using a mechanical method at 450 rpm to ensure uniform distribution of SiC particles. The mechanical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…steel disc into the MMCs and enhance the wear resistance. The Al 2 O 3 -SiC particulates may get crushed to powder form to maintain the wear resistance as detected in the results of wear rate [32,33]. Similar results have been noticed [5] and it is concluded that, from the analysis it is seen that, the SEM analysis of worn-out surfaces of the MMCs (Al7075 + 2%Al 2 O 3 + 3%SiC) is different from that of Al7075 + 5%Al 2 O 3 + 7%SiC composite.…”
Section: Morphological Analysissupporting
confidence: 63%
“…steel disc into the MMCs and enhance the wear resistance. The Al 2 O 3 -SiC particulates may get crushed to powder form to maintain the wear resistance as detected in the results of wear rate [32,33]. Similar results have been noticed [5] and it is concluded that, from the analysis it is seen that, the SEM analysis of worn-out surfaces of the MMCs (Al7075 + 2%Al 2 O 3 + 3%SiC) is different from that of Al7075 + 5%Al 2 O 3 + 7%SiC composite.…”
Section: Morphological Analysissupporting
confidence: 63%
“…B. Rajeswari et al [12] also optimized the four process parameter with respect to the three output variables and verified experimentally that by using the optimized process parameter the predicted experimental results were obtained. Sekar et al [13][14] carried out the study of specific wear rate with respect to the variation of Load, Sliding Distance and wt.% of SiC with central composite design. Also, optimized the variation of input factor with the output response to predict the abrasive response of the wear.…”
Section: Response Surface Methodology (Rsm) By Box-behnkenmentioning
confidence: 99%
“…Stir casting is most widely used liquid state method for fabrication of aluminium composite [10][11][12][13] in which ceramic particles Al2O3/ZrO2 (dispersed constituent) called reinforcements mixed with AA7050 matrix using mechanical stirrer [1,2]. Stir casting technique is also known as vortex technique [14][15][16][17]. It is a simple, economical and most widely used technique to make metal matrix composite.…”
Section: Fabrication Processmentioning
confidence: 99%